Isolated Jejunal Perforation Following Bicycle Handlebar Injury in Adults: A Case Report. (5th August 2013) - Neofytou, Kyriakos; Michailidou, Maria; Petrou, Athanasios; Loizou, Sakis; Andreou, Charalampos; Pedonomou, Marios
Abstract : The small intestine is the third in frequency intraperitoneal organ which is injured after blunt trauma of the abdomen. In most of the cases, this type of injuries is accompanied by other injuries, which make it more difficult to diagnose. Failure of diagnosis and delay in treating these injuries significantly increase the morbidity and mortality of these patients. Abdominal visceral injuries after flipping the handlebar of the bike are common in children. Such injuries can cause injury to both solid and hollow abdominal viscera. Unlike children, adults' abdominal visceral injuries after flipping the bike's handlebar are extremely rare. A 25-year-old man was admitted to our department due to progressively abdominal pain after an accident with the handlebar of his bike. The subsequent CT scan after per os administration of contrast medium revealed the presence of free intraperitoneal contrast. It is a rare case of jejunal perforation after flipping the handlebar of the bicycle which was treated by partial removal of the injured part of jejunum and end-to-end anastomosis. To the best of our knowledge this is the first time we describe such an injury with this mechanism to an adult.